Runtuhnya Marxisme-Leninisme di Uni Soviet dalam Teori Ashabiyah Ibnu Khaldun - Febrian, Emil Dwi; Susanto, Susanto; Habsari, Sri Kusumo (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2021)
This article examines history collapse of the Soviet Union with Ibn Khaldun's ashabiyah theory. The Soviet Union was first communist nation founded in 1922 after fall of the Russian-Monarchy due to the crisis and saparatist movement in 1917. Post World War II, the Soviet Union became a center of the communist movement around the world, and advanced in industrial sector, known as a superpower nation in the 20th century beside the United States. However, the Soviet Union was declared collapsed in 1991. This article found that Ibn Khaldun's ashabiyah can explain history of the Soviet Union in three stages of state metamorphosis; formation, glory, and collapse. Ashabiyah means a bond that unites the people, but it can be positive and negative. Analysis with negative ashabiyah, concluded that the collapse of Marxism-Leninism in Soviet Union was due to the denial of this philosophical teaching to create the privileges of the Communist Party became an authoritarian regime, and considered irrelevant and opposed by society. Authoritarianism happaned because of exclusivism and cult, and could occur in non-communist nations, including Indonesia in the New Order era, this shows that it is not ideology that created of authoritarian regimes, but political practices in specific nations.